PENGARUH KURANGNYA RUANG BELAJAR TERHADAP KONSENTRASI PESERTA DIDIK DI SEKOLAH DASAR KUBANG KUTU 2 KOTA CILEGON - Chrisyanto, Bait Dwi; Sariwardani, Andriani (LPPM Universitas Bina Bangsa, 2024)
The learning environment factor is one of the most important for the success of the student learning process because it is a very important means and infrastructure for improving students' knowledge (cognitive), relative attitudes (affective) and skills (psychomotor). Therefore, learning environments can be divided into two categories: natural environments and non-natural environments. Natural categories include air, temperature, weather, time of day (morning, afternoon, and evening), and time of day. The place where people learn is their social and cultural environment. So, if these factors are not balanced, learning will not produce the best results. This research is a type of quantitative research that uses analytical descriptive methods, which means the researcher will only provide an explanation of certain variables and present the results in the form of a frequency distribution table. By collecting data using primary data. Due to the lack of study space, there is a change in the study room, which results in students coming in during the day when that time should be used for rest. Thus, it can be concluded that the lack of classrooms affects the learning concentration of students at Kubang Kutu 2 Elementary School, Cilegon City